Regional Difference in Ethics Decision Making : Study of IT Pre-Professionals in China - Nguyen, Thang Minh (My University, 2012)
Information and communications technology played a significant role in the recent economic growth of China, which now ranks as the second largest economy in the world. As a result, China faces many social and ethical challenges common to technology-advanced countries. The purpose of this study was to investigate ethics decision making by IT professionals in different regions of China.
Color poster with text, graphs, and diagrams.
Keywords: Business ethics--China--Regional disparities; Management information systems--China; China--Social conditions--21st century; Posters